Nitric Oxide in the Pathogenesis and Treatment of Tuberculosis - Jamaati, Hamidreza; Mortaz, Esmaeil; Pajouhi, Zeinab; Folkerts, Gert; Movassaghi, Mehrnaz; Moloudizargari, Milad; Adcock, Ian M.; Garssen, Johan (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is one of the most important human pathogens globally. Mtb is estimated to infect nearly one third of the world`s population with many subjects having a latent infection. Thus, from an estimated 2 billion people infected with Mtb, less than 10% may develop symptomatic TB. This indicates that the host immune system may constrain pathogen replication in most infected individuals. Macrophages, as key innate immune effector cells, are the first cells that encounter Mtb. On entering the lungs of the host, Mtb initially encounters resident alveolar macrophages which can engulf and subsequently eliminate intracellular microbes via a plethora of bactericidal mechanisms including the generation of free radicals such as reactive oxygen and nitrogen species. Nitric oxide (NO), a key antimycobacterial molecule, is detected in the exhaled breath of patients infected with Mtb. NO is synthesized from its precursor L-arginine in a wide array of cells in many vertebrates by the action of three different stereospecific NO synthases. Recent knowledge regarding the regulatory role of NO in airway function and Mtb proliferation paves the way of exploiting the beneficial effects of this molecule for the treatment of airway diseases. Here, we discuss the importance of NO in the pathogenesis of TB, the diagnostic use of exhaled and urinary NO in Mtb infection and the potential of NO-based treatments.